2020
DOI: 10.1016/j.heliyon.2020.e04310
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of partial gag, pol and env genes show predominance of HIV-1G and CRF02_AG with emerging recombinants in south-eastern Nigeria

Abstract: Human Immunodeficiency Virus is characterized by high degree of genetic diversity with marked differences in its geographic distribution even within a country. This study was designed to identify the strains of HIV-1 circulating among infected individuals in southeastern parts of Nigeria. Genomic DNA was extracted from blood samples of 30 HIV-1 infected individuals from Anambra, Delta and Imo states of southeastern Nigeria. Portions of the genome corresponding to entire p24 gag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 48 publications
(63 reference statements)
1
4
0
Order By: Relevance
“…This study shows the circulation of HIV-1 subtypes/sub-subtypes A, A3, G, CRF02_AG, D, F2, CRF37_CPX, CRF06_CPX, CRF09_CPX, CRF45_CPX, CRF11_CPX, CRF56_CPX, and CRF05_DF in different proportions among PWH in Nigeria. The predominance of CRF02_AG (22 out of 33 in integrase , 23 out of 33 in protease , 10 out of 17 in reverse transcriptase , seven out of 24 in V1V3 , three out of eight in whole genome sequences) and subtype G (8 out of 33 in integrase , five out of 33 in protease , four out of 17 in reverse transcriptase , two out of 24 in V1V3 , and one out of eight in whole genome sequences) is in line with previous studies carried out in Nigeria [ 14 , 18 , 20 21 , 25 , 50 56 ]. CRF02_AG and subtype G are the dominant circulating forms of HIV-1 in Nigeria and they are largely driving the epidemic in the country.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This study shows the circulation of HIV-1 subtypes/sub-subtypes A, A3, G, CRF02_AG, D, F2, CRF37_CPX, CRF06_CPX, CRF09_CPX, CRF45_CPX, CRF11_CPX, CRF56_CPX, and CRF05_DF in different proportions among PWH in Nigeria. The predominance of CRF02_AG (22 out of 33 in integrase , 23 out of 33 in protease , 10 out of 17 in reverse transcriptase , seven out of 24 in V1V3 , three out of eight in whole genome sequences) and subtype G (8 out of 33 in integrase , five out of 33 in protease , four out of 17 in reverse transcriptase , two out of 24 in V1V3 , and one out of eight in whole genome sequences) is in line with previous studies carried out in Nigeria [ 14 , 18 , 20 21 , 25 , 50 56 ]. CRF02_AG and subtype G are the dominant circulating forms of HIV-1 in Nigeria and they are largely driving the epidemic in the country.…”
Section: Discussionsupporting
confidence: 91%
“…The observation of a wide array of subtypes among a small number of individuals in this study further emphasizes the high genetic diversity of the virus in Nigeria. Previous studies have shown that movement of people from one country to another has contributed largely to the spread of HIV-1 diversity worldwide [ 20 ]. In developing countries, the migration of rural populations because of poverty, famine, civil wars, and so forth have been additional contributing factors to the genetic diversity of the virus [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations